Validation of analytical methodology to determine the quantification of tannins in the pit avocado (Persea americana Miller var. hass) by high pressure liquid chromatography - Castro Zavaleta, Víctor Augusto (2014)
In the present research work entitled Validation of an analytical methodology for determining tannins (catechin) in pit (integument) avocado (Persea americana Miller var. Hass) by high resolution liquid chromatography “(HPLC), is to validate a methodology HPLC to determine the concentration of these analytes, using an Agilent 1100 gas chromatograph with diode array detector was used with a UV-Visible octadecylsilane column (C18) of 150 mm length and 4.6 mm internal diameter; was used as mobile phase solution A (methanol) and solution B (glacial acetic acid 0.1%), with a travel time of 15 minutes, in an isocratic gradient of 15% A and 85% B; read at a wavelength of 210 nm, with a flow rate of 1 mL / min. was injected 10 uL sample at a temperature of 35 ° C. Finding that the evaluated parameters: linearity, limit of detection, limit of quantification, precision and accuracy of the method are within accepted values for validation.